Dostosowanie sposobu organizacji czasu pracy do obowiązków rodzinnych w Polsce - Baranowska-Rataj, Anna; Rynko, Maja (Studia Demograficzne, 2013)
This paper presents a diagnosis of reconciliation of work and parenthood in Poland based on the data from the European Labour Force Survey ad hoc module “Reconciliation between work and family life” carried out in 2010. These data provide information on the following options of combining work with parenthood duties: (1) part-time work (2) flexible arrangements of working time (3) distance work. We compare the conditions for combining work with parenthood duties in Poland with opportunities observed in other European countries. We also show to what extent the conditions for reconciliation of work and parenthood in Poland have improved in time. We make an overview of legal regulations related to combining work with childcare duties and indicate the opportunities for improvement of these policies.